Photodynamic inactivation of Lasiodiplodia theobromae: lighting the way towards an environmentally friendly phytosanitary treatment. (21st April 2021) - Garcia, M.; David, B.; Sierra-Garcia, I. N.; Faustino, M. A. F.; Alves, A.; Esteves, A. C.; Cunha, A.
Abstract : The fungus Lasiodiplodia theobromae is one of the main causal agents of trunk canker and dieback of grapevine. The objective of this work was to evaluate the efficiency of photodynamic inactivation (PDI) of L. theobromae with synthetic and natural photosensitizers and irradiation with either sunlight or artificial photosynthetically active radiation. Although the growth of the mycelium could not be completely prevented with natural sunlight irradiation, phenothiazine dyes (methylene blue, MB; toluidine blue O, TBO), riboflavin and a cationic porphyrin (Tetra-Py + -Me) caused complete inhibition under continuous irradiation with artificial light. Free radicals were the main cytotoxic agents in the PDI with MB, indicating the predominance of the type I mechanism. PDI with MB or Tetra-Py + -Me may represent a promising approach for the sanitation of vine material in greenhouse nurseries, in order to reduce the risk of infection upon grafting.